2011
DOI: 10.1007/s11661-011-0918-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Mechanical Properties of A356 Tensile Test Bars Cast in a Permanent Mold by Application of a Knife Ingate

Abstract: As a standard test-bar permanent mold, the ''Stahl'' Mold has been widely used in foundries to assess the properties of cast alloys. However, inferior mechanical properties are often obtained with this mold due to shrinkage-induced microporosity in the gage section. In order to improve the mechanical properties, a design modification comprising a thin knife ingate between the feeder and test-bar cavity was evaluated in this work. The new design was studied by computeraided simulation. Simulations predicted tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Lower shrinkage porosity in the thinnest step can be referred to the good metal filling capability, which in turn may be attributed to the application of the thin and large fan-type ingate connecting the runner and die cavity. Wang et al [8] obtained similar porosity reduction in the Stahl permanent test-bar mold by applying a thin ''knife'' ingate on the test bars. Such ingate configuration is similar to the fan ingate suggested in the current work.…”
Section: B Simulation Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Lower shrinkage porosity in the thinnest step can be referred to the good metal filling capability, which in turn may be attributed to the application of the thin and large fan-type ingate connecting the runner and die cavity. Wang et al [8] obtained similar porosity reduction in the Stahl permanent test-bar mold by applying a thin ''knife'' ingate on the test bars. Such ingate configuration is similar to the fan ingate suggested in the current work.…”
Section: B Simulation Results and Discussionmentioning
confidence: 84%
“…However, to overcome the difficulty in producing the best mechanical properties of cast alloys, [5] several efforts have been paid by foundries to improve the initial Stahl design. [6][7][8][9] Furthermore, because the test bars obtained by the Stahl mold show well-defined dimensions, in terms of gauge length and section, this configuration does not allow to reproduce different solidification conditions integrated into a single die design.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study was limited to microstructural characterization of magnesium alloys and needs to be extended to aluminum alloys. By means of numerical simulation techniques, Wang et al [ 31 ] found that the gauge section of the standard Stahl mold (standard ASTM B-108) showed higher porosity (about 3%) compared to the AA Step mold (less than 1%) in an AlSi7Mg alloy. This comparison confirmed the statement of Singworth and Kuhn [ 32 ] that the Stahl mold could not produce better mechanical properties than the Step mold, due to higher micro-porosity in the gauge section on account of micro-shrinkage.…”
Section: Results On the Expected Tensile Strength Of Al-si Alloys mentioning
confidence: 99%
“…Figure 8. Comparing the porosity in (a) ASTM mold and (b) modified design, estimated using numerical simulation; (c) arrow shows modified riser thickness [20] (d) Details of the knife ingatecasting and (e) the improvement in the tensile properties[21] …”
mentioning
confidence: 99%